2011
DOI: 10.1155/2011/501726
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids for the Treatment of Schizophrenia? A Balanced Neurochemical Framework for Both Adverse and Therapeutic Effects of Cannabis Use

Abstract: Recent studies have found that cannabinoids may improve neuropsychological performance, ameliorate negative symptoms, and have antipsychotic properties for a subgroup of the schizophrenia population. These findings are in contrast to the longstanding history of adverse consequences of cannabis use, predominantly on the positive symptoms, and a balanced neurochemical basis for these opposing views is lacking. This paper details a review of the neurobiological substrates of schizophrenia and the neurochemical ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 99 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…While some studies suggest that C. sativa L. use may increase the risk of developing psychotic disorders and even worsen prognosis and disease burden, likely due to psychoactive compounds [134,137], others suggest non-psychoactive compounds in the plant may have therapeutic efficacy.…”
Section: Schizophreniamentioning
confidence: 99%
“…While some studies suggest that C. sativa L. use may increase the risk of developing psychotic disorders and even worsen prognosis and disease burden, likely due to psychoactive compounds [134,137], others suggest non-psychoactive compounds in the plant may have therapeutic efficacy.…”
Section: Schizophreniamentioning
confidence: 99%
“…It has been suggested that cannabis might have a cognitive enhancing effect due to stimulating prefrontal neurotransmission (Coulston et al, 2007). The cognitive deficits in schizophrenia have been associated with a decrement in prefrontal dopamine activity (Coulston, Perdices, Henderson, & Malhi, 2010). It is therefore hypothesized that low, infrequent doses of cannabis may result in an increase in activity in the frontal lobe and subsequent improvement in cognitive function in those with a psychotic disorder (Cohen, Solowij, & Carr, 2008).…”
Section: Meta-analysismentioning
confidence: 99%
“…Given the established role of CB 1 R in the acquisition, encoding, and retrieval of memories (Riedel and Davies, 2005), variations in this receptor population possibly mediate the detected effects of cannabis use on memory (Castillo et al, 2012; Montgomery and Fisk, 2007). The cannabinoid system interacts with several neurotransmitter systems (Coulston et al, 2011) such as acetylcholine, dopamine, serotonin, gamma-aminobutyric acid (GABA), glutamate, and noradrenaline by activation of CB 1 R (Al-Hayani and Davies, 2002; Schlicker and Kathmann, 2001).…”
Section: Introductionmentioning
confidence: 99%